Interaction between berberine hydrochloride and β-lactoglobulin of two structures by heat treatment. (February 2022) - Xiang, Xi; Sun, Qiaomei; Gan, Na; Suo, Zili; Zhang, Shuangshuang; Yao, Shun; Xiang, Hongzhao; Yuan, Na; Li, Hui
Abstract: Heat treatment, a method of treating proteins during food processing, can cause conformational and morphological changes. Dairy products contain β-lactoglobulin (β-lg), which is usually used at high temperature or pasteurization, and β-lg can form three-dimensional hydrophilic gel by heat treatment under certain conditions. This study revealed the structural differences between native (n-lg) and heated proteins (h-lg) and compared their binding mechanism with berberine hydrochloride (BH), thereby providing sights into the functional food formulation design. After heat treatment the secondary structure of β-lg became compact. In addition, the morphology of protein nanoparticles changed from uniform spherical to irregular angular. The interaction mechanism of BH with β-lg was investigated by multi-spectroscopic methods and computer simulation techniques. The interactions between β-lg and BH showed a static quenching mechanism with energy transfer under electrostatic and hydrophobic force. Moreover, protein–ligand complexes showed moderate binding capacity with the binding stoichiometric ratio of 1:1. Results were consistent between n-lg-BH and h-lg-BH systems. The differences caused by heat treatment were reflected in the perturbation of the protein structure and the temperature sensitivity of binding affinity. Molecular simulation showed that BH tends to bind on the outside of the barrel and close to Trp19–Arg124 of β-lg and verified the reliability of the experimental results theoretically. This study showed the importance of heat treatment in food processing and explored the mechanism of heated protein and ligand in the protein–ligand interaction. Graphical abstract: Image 1 Highlights: We studied the interaction between protein and nutrients following heat treatment. Heat treatment produced complex under hydrophobic force and electrostatic force. The affinity and conformation alterations by heat treatment were found.